Islamic Religious Education Learning Management Based on Holistic Education at Superior Islamic High School Al-Fahd Jakabaring - Arafat, Yanuar; Idi, Abdullah; Badaruddin, Kms. (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The aim of this research is to obtain data about learning management which includes planning, implementation and evaluation. This research is qualitative research with a case study type. The data in this research was obtained by interviews, observation and documentation. Data were analyzed using descriptive data analysis techniques. The results of this research explain that the learning plans prepared before implementing learning in the classroom include the syllabus, annual program, semester program, effective week, and Learning Implementation Plan. Learning is carried out by applying active learning methods such as discovery learning methods, problem based learning, and project based learning. Aspects developed in learning include linguistic, interpersonal, intrapersonal, visual, kinesthetic and entrepreneurial intelligence. The learning evaluations used are project assessments, practical assessments, teacher observation assessments, description test assessments, and portfolio assessments. Learning evaluation measures aspects of knowledge, attitudes and skills.